Revitalizing eXene - Hoag, Matthew (Kansas State University, 2009)
This thesis covers the process leading up to the release of eXene 2.0, a User Interface Management System (UIMS) toolkit. Since its inception, eXene has provided a unique way to create meaningful graphical user interfaces (GUIs) for Standard ML applications. Additionally, it has gone through several quality revisions which have both enhanced the toolkit and corrected many deficiencies that were present. Even with these improvements, however, the full potential of eXene has become increasingly difficult for developers to utilize. That is, in spite of the natural innovation that eXene brings to GUI construction, its current lack of extensibility, usability, and functionality has caused Standard ML developers to choose simpler, more familiar UIMS toolkits, despite their limitations, for the creation of their applications. In light of this fact, eXene needs an internal and cosmetic overhaul to extend its usage and appeal. First, to improve its extensibility, formerly weakened by organic growth, eXene requires some restructuring of its architecture. Second, to improve its overall usability, previously stifled by sparse documentation, eXene requires the implementation of an interactive electronic document for its API. Finally, to improve its functionality, several new multi-purpose widgets need to be introduced. It is the author's hypothesis that the revised structure, improved documentation, and additional multi-purpose widgets detailed in this thesis sufficiently elevate eXene's extensibility, usability, and functionality such that eXene can be considered a fully featured UIMS toolkit. With these changes and the release of eXene 2.0, eXene is more likely to be adopted as the primary UIMS toolkit for Standard ML developers.
Keywords: eXene; Graphical user interface; User interface management system toolkit; Computer Science (0984)